2007
DOI: 10.1590/s1413-81232007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Possibilidades de contribuição do farmacêutico para a promoção da saúde

Abstract: Medicines are considered the main therapeutical tool for the treatment or maintenance of public health conditions. However, the symbolism in wich they are cloaked and thus their use by society, has contributed to the emergence of many adverse events with high impact on health and health systems costs. Thus, rational drug use promotion is an important tool to eliminate or minimize the problem. This is where the pharmacists can play an important role because this is a pertinent subject in their field of performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
89

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 6 publications
3
24
0
89
Order By: Relevance
“…Besides, they also had difficulties in narrating the way they use their medicines at home. These findings also indicate that the quality of the dispensing practices at the PHCPS can be considered suboptimal and are in line with other authors 12,40 . It should be mentioned that the pharmacists, as they stated themselves, did not involve in dispensing activities, a result already evidenced by other authors [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, they also had difficulties in narrating the way they use their medicines at home. These findings also indicate that the quality of the dispensing practices at the PHCPS can be considered suboptimal and are in line with other authors 12,40 . It should be mentioned that the pharmacists, as they stated themselves, did not involve in dispensing activities, a result already evidenced by other authors [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 91%
“…However, weaknesses in the structuring of the services still persist 8 . Several authors have shown problems at PHCPS, such as low availability of medicines [9][10][11] , inattention to the legal rules for medicines procurement 12 ; inadequacies in the dispensing area 9,13 , in medicines storage 9,12,13 and in inventory control 12 . Additionally, there is a large number of patients who do not have satisfactory knowledge about their prescribed treatment 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…O problema de condições de armazenamento não é único em Petrolina. Na pesquisa de Vieira 15 , foi constatado que 47% dos municípios estudados estavam sujeitos a condições inadequadas de armazenamento 14 .…”
Section: Resultsunclassified
“…Pharmacists must dedicate the time to consider the desires, preferences and needs of the patient in terms of their health, and pharmacists should be committed and continue to focus once practicing (Peretta, Ciccia, 2000). Currently, the Brazilian Consensus on Pharmaceutical Care recommends that this practice is based on health education, guidance, care and dispensing phar- Women cancer prevention and pharmaceutical contribution 47 macists, as well as on pharmacist therapeutic monitoring, while recording the activities proposed to evaluate results (Vieira, 2007). Pharmaceutical care must be implemented on three basic fronts: pharmacy orientation service, development of skills in the community, and encouraging community action (PAHO, 2002).…”
Section: The Role Of the Pharmacist In Cancer Preventionmentioning
confidence: 99%